Genetic Polymorphism of g.3768T>C loci of NRAMP1 gene in Kampung and KUB Chickens - Maskur, Maskur; Muhsinin, Muhammad; Rozi, Tapaul; Jan, Rahma; Kasip, L. (Jurnal Biologi Tropis, 2024)
Natural Resistance-Associated Macrophage Protein 1 (NRAMP1) is a gene that regulates the body's resistance to illness. The genetic diversity of Kampung and KUB chicken population in Lombok island West Nusa Tenggara province was investigated based on g.3768T>C loci of NRAMP1 gene. Experimental animal consisted of 105 KUB and 67 Kampung chickens. The NRAMP1 gene polymorphisms in both population were identified using PCR-RFLP method. Genetic parameters of g.3768T>C loci were calculated using PopGene32. In this study, the locus g.3768T>C of the NRAMP1gene found three genotypes (TT, CT, CC) with the frequency of the C allele was higher than the T allele, respectively 0.709 and 0.210 in Kampung chicken, and 0.738 and 0.262 in KUB chicken. The mean value of observed heterozygosity (Ho) and expected heterozygosity (He) of g.3768T>C loci in both populations revealed low to medium genetic diversity, with the values 0.222 and 0.400, respectively. The mean value of observed heterozygosity is lower than expected, indicating that the population is heading towards a heterozygosity deficit and proving that the two populations are not in Hardy-Weinberg equilibrium. The mean PIC value of the NRAMP1 gene (g.3768T>C) in both chicken population was 0.319 and classified as fairly informative (0.50 > PIC > 0.25). Meanwhile, the value of the genetic differentiation index (Fst) for Kampung and KUB chicken population were 0.385 and 0.433, indicating that there is differentiation between two chicken population at the observed loci.